An analysis of the narco theme through mexican documentary theater (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
In this writing, under the precepts of documentary theater, five works of recent Mexican dramaturgy are analyzed: El Jinete de la Divina Providencia (1984), de Óscar Liera; México, USA (1996), de Felipe Santander; Contrabando (1991), de Víctor Hugo Rascón Banda; Música de balas (2012), de Hugo Salcedo y Tártaro. Réquiem de cuerpo presente por el niño que aprendió a matar (2020), de Sergio López Vigueras. All of them address the issue of drug trafficking with the intention of highlighting the disorders it produces in the civilian population. For this reason, we maintain as a main premise that in these dramaturgies the perspective of the victims predominates, positioning the voices that are generally left out in the center.
Keywords: Documentary theater; Drug trafficking; Violence; Civil society; Victims